El derecho a la reparación integral de la víctima en la aplicación del procedimiento directo en delitos de tránsito - Pachay Guaño, Cristian Anderson (2025)
This research focuses on the analysis and diagnosis of the direct procedure and the rights of victims enshrined in the Organic Criminal Code and its superior hierarchical fundaments within the Constitution of the Republic of Ecuador. To achieve this objective, this research develops a critical-legal analysis that leads to determine if the application of the direct procedure in traffic offenses involving personal injuries ensures compliance with victims’ right to full reparation in Ecuador. Likewise, to get an effective contrast of the information collected previously, this research work applies a closed-ended interview to specify the diagnostic assessment on the direct procedure in its application to traffic offenses. With the synthesis of the results collected, this research work seeks to identify positive and negative aspects to outline potential improvements to the special procedure under analysis. Through a comparative documentary analysis and the findings from the applied interview, this study proposes to reform the articles regarding the direct procedure specifically regarding the factors that determine the maximum time allowed to develop the direct trial hearing to guarantee the proportionality used to adjudicate the offense and reparation for the victims is fully applied.